2019
DOI: 10.1002/celc.201900378
|View full text |Cite
|
Sign up to set email alerts
|

Zwitterionic Copolymer‐Supported Ionogel Electrolytes: Impacts of Varying the Zwitterionic Group and Ionic Liquid Identities

Abstract: A series of copolymer scaffolds containing zwitterionic (ZI) functional groups, synthesized in situ in two alkylimidazolium cation-based ionic liquids, has been created by using two different ZI monomers to yield nonvolatile ionogel electrolytes that exhibit high ionic conductivities and a wide range of elastic moduli. Although all of the examined ionogel formulations consist of 80 mol % ionic liquid, gel properties are observed to depend both on zwitterion content within the copolymer scaffold, as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…A deep understanding of the structure of the electrode-liquid interface is a vital basis for applications in electrochemical engineering, for example, electrochemical reaction, [1] energy storage, [2][3][4] gas separation, [5] supercapacitor, [6][7][8] sensor devices, [2,[9][10] and so on. During the practical electrochemical process, ionic liquids (ILs) have been widely used as the new solvent or electrolyte due to their extremely low volatility, high thermal stability and wide chemical window.…”
Section: Introductionmentioning
confidence: 99%
“…A deep understanding of the structure of the electrode-liquid interface is a vital basis for applications in electrochemical engineering, for example, electrochemical reaction, [1] energy storage, [2][3][4] gas separation, [5] supercapacitor, [6][7][8] sensor devices, [2,[9][10] and so on. During the practical electrochemical process, ionic liquids (ILs) have been widely used as the new solvent or electrolyte due to their extremely low volatility, high thermal stability and wide chemical window.…”
Section: Introductionmentioning
confidence: 99%
“…Rebollar et al [149] polymerize the zwitterionic (ZI) monomers of sulfobetaine vinylimidazole (SBVI) and 2-methacryloyloxyethyl phosphorylcholine (MPC) in two kinds of ILs [C 1 C 2 Im][TFSI] and [C 1 C 2 Im][TCB] to prepare ionogel, respectively (Figure 8a). The ionogel exhibits excellent mechanical properties by the dipole-dipole interaction between the amphoteric polymers.…”
Section: Direct Polymerization Of Polymerizable Monomersmentioning
confidence: 99%
“…(b) The conductivities of ZI ionogels with different zwitterion contents. Adapted with permission from Ref [149]…”
mentioning
confidence: 99%
“…For instance, Panzer group reported zwitterionic copolymer ionogels which exhibit ionic conductivity up to 6.7 mS cm −1 and compressive elastic moduli up to 11 MPa. [ 31‐34 ] Our previous work also demonstrated that zwitterionic polymer could help increasing the mechanical strength and ionic conductivity of polyelectrolyte hydrogels. [ 35 ]…”
Section: Introductionmentioning
confidence: 99%